Vapour flux divergence and moisture budget calculations for Labrador-Ungava - Barry, R. (Cahiers de géographie du Québec, 1968)
For the two winter seasons 1956-57 and 1957-58, the author uses aerological data to estimate the moisture budget for the Labrador - Ungava peninsula.Two methods of estimating the vapour flux-divergence between the surface and 500 mb. are described. In the first, the horizontal divergence is determined from separate maps of the flux components with reference to a latitude - longitude grid. A comparison of the resulting maps of flux-divergence with the winter maps of mean monthly precipitation show an agreement in pattern, although allowing for evaporation losses, the amounts appear to be generally too low except in the south-east. The second method, using a triangle technique (Stephenville - Goose - Sept- Iles) at eight levels proved less reliable. A detailed comparison is made of estimates of the total and eddy flux-divergence (based on the first method) and precipitation minus evaporation estimates, and significant differences are discussed. The results show that correspondence between aerological and surface estimate of precipitation minus evaporation a Labrador - Ungava is not as satisfactory as might be hoped.